[mu-1,1 `-Bis(diphenylphosphino)ferrocene]bis{[(Z)-O-ethyl N-phenylthiocarbamato-kappa S]gold(I)} dichloromethane solvate - Ho, S.Y.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The binuclear title compound, [Au(2)Fe(C(9)H(10)NOS)(2)(C(17)H(14)P)(2)]center dot CH(2)Cl(2),which has the Fe atom located on a crystallographic centre of inversion, crystallizes as a 1: 1 dichloromethane solvate, which is disordered about a centre of inversion. There is a small deviation from linearity defined by the SP donor set [S1-Au-P1 angle is 175.35 (5)degrees] which is due to an intramolecular Au center dot center dot center dot O contact [3.080 (5) angstrom]. The primary intermolecular contacts between binuclear molecules are of the type C-H center dot center dot center dot pi, and are arranged so as to form columns in the a-axis direction in which the disordered solvent molecules reside.